Cytotoxicity test of binjai leaf (Mangifera caesia) ethanol extract in relation to Vero cells - Fifi Dwidhanti; Irham Taufiqurrahman; Bayu Indra Sukmana (Faculty of Dental Medicine, Universitas Airlangga https://fkg.unair.ac.id/en, 2018)
Background: Binjai leaves (Mangifera caesia) constitute one part of a medicinal plant from South Borneo that contains potential anticancer and antioxidant flavonoids. Before using medicinal plants as adjuvant therapy material, a cytotoxicity test of a material extract needs to be conducted in order to establish the safety of natural ingredients that will be used in the production of medicinal products. Purpose: This research aimed to determine whether the ethanol extract of binjai leaves proved cytotoxic to Vero cells and determine the value of IC50 after the administering of ethanol extract of Binjai leaves by means of an MTT assay method. Methods: This research incorporated a true experimental method with posttest-only control design that consisted of ten groups. The Binjai leaf ethanol extract of varying concentrations was administered to eight groups, namely;1.25µg/mL, 62.5µg/mL, 125µg/mL, 250µg/mL, 500µg/mL, 1000µg/mL, 2000µg/mL and 4000µg/mL. The control groups consisted of two groups, one cell control group and one media control group. The cell viability percentage was calculated by an absorbent of ELISA reader. Results: The probit analysis result had an IC50 value of 2498.48µg/mL (IC50>1000µg/mL constituted a non-toxic category). Conclusion: Ethanol extract of Binjai leaves is not cytotoxic to Vero cells as shown by an assay MTT method which produced an IC50 value of 2498.48µg/mL.